Gill structure of Rasbora argyrotaenia from the Siak River, Tualang Village - Mohd Zulkurnain; Windarti '; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Siak River is the most polluted river in Riau, however, many types of fish, including Rasbora argyrotaenia living in that river. As the water is polluted, the health of the fish in general, including its gill structure might be harmed. A study aims to understand the histological structure of the gill of fish from the Siak River has been conducted in February 2015. Abnormality in the gill was noted and the abnormality level was identified using a Histopathological Alteration Index (HAI). Results shown that the types of abnormality present were hyperplasia, hypertrophy, atrophy, epithelium rupture and congestion. The HAI level (13 - 14) indicate that the gill of the R. argyrotaenia from the Siak River was slight damage. This abnormality might be cured if the water quality in the Siak River is good.Keyword: Siak River, Histopathological Alteration Index (HAI), Histology, Abnormality in the gill.